The Public Relations Acceptance Towards Press Release Application with Artificial Intelligence - Pijar Suciati; Mareta Maulidiyanti; Ngurah Rangga Wiwesa (Communicare : Journal of Communication Studies, 2021)
Artificial Intelligence (AI) is gradually changing every industry, including the Public Relations industry (Afzal, 2018). Skills associated with conducting research, creating content, evaluating campaigns, tracking issues and countless work processes are being automated with AI. We believe, although never fully replace public relations professionals but will increasingly assist us and possibly do a better job. We are developing PR Bot, a tool that help PR to create an instant press release using an AI (machine learning). Before we continue building the app, we need to know whether the PR practitioners will accept this technology or not. To find the results we conduct a descriptive research, using interview and polling survey, convenient sampling among the PR professional in Greater Jakarta area. We use Technology Acceptance Model to develop the questionnaire. According to the interview, we found that the knowledge and skill of using new technology of the respondents is very good. The survey shows the acceptance of the perceived ease of use and perceived usefulness of the PR Bot is high. The conclusion, the target market is ready to use the technology, they feel that this tech will help them in daily basis task. Based on this result, we will continue developing and using the insight from the respondents to build the feature of this application.